1993
DOI: 10.1128/aem.59.5.1520-1525.1993
|View full text |Cite
|
Sign up to set email alerts
|

Probing activated sludge with oligonucleotides specific for proteobacteria: inadequacy of culture-dependent methods for describing microbial community structure

Abstract: Bacterial community structures in activated sludge samples from aeration tanks of a two-stage system with a high-load first stage and a low-load second stage were analyzed with oligonucleotide probes. The probes were complementary to conserved regions of the rRNA of the alpha, beta, and gamma subclasses of proteobacteria and of all bacteria. Group-specific cell counts were determined by in situ hybridization with fluorescent probe derivatives. Contributions of the proteobacterial subclasses to total bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
269
2
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 686 publications
(295 citation statements)
references
References 23 publications
17
269
2
2
Order By: Relevance
“…The comparison of the quantitative and qualitative information on bacterial diversity in T. magnatum, collected with the above-mentioned methods, showed that only a few 16S rDNA sequences of the isolates were comparable to those of environmental clones. This confirmed the importance of non-cultivation approaches in studying bacterial diversity in truffle (Barbieri et al, 2005a), notably because cultivation-based diversity surveys are rather unlikely to reflect the true microbial community structure present in situ because of inherent qualitative and quantitative biases (Wagner et al, 1993;Hugenholtz et al, 1998;Ellis et al, 2003). Nevertheless, the 16S rDNA sequences obtained from the bacterial isolates extended the taxonomic databases of Tuber-associated bacteria useful for comparative systematic studies.…”
Section: Discussionmentioning
confidence: 54%
“…The comparison of the quantitative and qualitative information on bacterial diversity in T. magnatum, collected with the above-mentioned methods, showed that only a few 16S rDNA sequences of the isolates were comparable to those of environmental clones. This confirmed the importance of non-cultivation approaches in studying bacterial diversity in truffle (Barbieri et al, 2005a), notably because cultivation-based diversity surveys are rather unlikely to reflect the true microbial community structure present in situ because of inherent qualitative and quantitative biases (Wagner et al, 1993;Hugenholtz et al, 1998;Ellis et al, 2003). Nevertheless, the 16S rDNA sequences obtained from the bacterial isolates extended the taxonomic databases of Tuber-associated bacteria useful for comparative systematic studies.…”
Section: Discussionmentioning
confidence: 54%
“…Zoogloea species have long been considered to be predominant floc-forming bacteria of activated sludge. Fluorescence in-situ hybridization analysis using the 16S rRNA-targeted oligonucleotide probes revealed that Zoogloea cells accounted for up to approximately 10% of the total cell numbers of activated sludge samples (Wagner et al, 1993;Rossellomora et al, 1995). High throughput 454 pyrosequencing of amplicons of 16S rDNAs also revealed that Zoogloea existed in high abundance (1.38-11.1%) in the activated sludge of municipal sewage treatment plants (Wang et al, 2012;Zhang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…failed to perform the biochemical transformations that take place in the treatment process and constituted only a smaller fraction of total bacterial cells in the sludge. This bias arises mainly because of the low fraction of culturable organisms present in the sludge (Wagner et al, 1993;1994a).…”
Section: Introductionmentioning
confidence: 99%